2022
DOI: 10.1002/adfm.202111661
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Deficient Sites for Improving V2+/V3+ Redox Kinetics in Vanadium Redox Flow Batteries

Abstract: Fundamental kinetics of the V2+/V3+ of vanadium redox flow battery (VRFB) are still not well understood despite tremendous efforts in improving the sluggish kinetics of V2+/V3+. This article first reveals the rate‐determining step in the electrochemical oxidation of V2+ to V3+ by exploring the reaction kinetics. Thereafter, TiB2 with abundant electron‐deficient sites, which possesses a strong electron‐accepting ability, is demonstrated to improve the rate‐determining step of V2+/V3+ by enhancing the electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 48 publications
(41 reference statements)
2
29
0
Order By: Relevance
“…Vanadium RFBs (VRFBs), the most representative aqueous RFBs, have a relatively mature preparation technology and are currently in the commercial demonstration stage. However, VRFBs have some limitations such as low energy density, high materials costs, narrow temperature adaptability, and strong corrosivity of the electrolytes, which hinder their widespread deployment 17–19 . In addition, the performance assessment of RFBs is not consistent in the reported works, making it challenging to evaluate the potential of various RFBs for practical application.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Vanadium RFBs (VRFBs), the most representative aqueous RFBs, have a relatively mature preparation technology and are currently in the commercial demonstration stage. However, VRFBs have some limitations such as low energy density, high materials costs, narrow temperature adaptability, and strong corrosivity of the electrolytes, which hinder their widespread deployment 17–19 . In addition, the performance assessment of RFBs is not consistent in the reported works, making it challenging to evaluate the potential of various RFBs for practical application.…”
Section: Introductionmentioning
confidence: 93%
“…However, VRFBs have some limitations such as low energy density, high materials costs, narrow temperature adaptability, and strong corrosivity of the electrolytes, which hinder their widespread deployment. [17][18][19] In addition, the performance assessment of RFBs is not consistent in the reported works, making it challenging to evaluate the potential of various RFBs for practical application. Therefore, Lu et al summarized and reported standard testing protocols including evaluating device performance of both symmetric and asymmetric cells.…”
Section: Introductionmentioning
confidence: 95%
“…To tackle these issues, electrode modications have attracted enormous attention, and tremendous effort has been made over the past decade to optimize carbon felt electrodes, [19][20][21][22][23] such as surface engineering, 17,24 heteroatom doping, 25,26 metal and metal oxide catalyst decoration, 27,28 etc. 29 While both surface engineering and heteroatom doping prove effective in enhancing anode V 2+ /V 3+ redox chemistry, only metal catalysts great promise to synergistically promote V 2+ /V 3+ kinetics and inhibit hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to better electrocatalytic activity or electronic conductivity, metal and metallic oxides deposition has been used to elevate the electrochemical performance of GFs [ 40 , 41 , 42 ], but their worse stability and expensive cost will challenge their practical application. Owing to the difference in electronegativity and atomic size with substrate atoms, hetero-atoms doping can break the Π bond conjugated system among carbon atoms in GFs, and then bring about defect sites in the graphite carbon skeleton, which contribute to boosting the electrochemical activity of composite electrodes [ 43 , 44 , 45 ]. Moreover, the element doped GFs still maintain stable electrochemical performance during long-term cycling because the hetero-atoms in the form of covalent bond are introduced into composite electrodes [ 46 ].…”
Section: Introductionmentioning
confidence: 99%